2020
DOI: 10.1097/qad.0000000000002410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes post transition to adult services in young adults with perinatally acquired HIV infection: mortality, retention in care and viral suppression

Abstract: Objective: Adolescence is the only age group globally where HIV associated mortality is rising, with poorer outcomes at all stages of the care cascade compared to adults. We examined post-transition outcomes for young adults living with perinatal HIV (YAPaHIV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Youth who perinatally acquired HIV are likely to be retained in HIV care. In a study in United Kingdom, among young adults with perinatally acquired HIV infection that assessed the clinical outcomes post transition to adult services, 86% of these youths were retained in HIV care [ 27 ]. In a systematic review by Ritchwood et al [ 28 ] to examine retention in HIV care, it indicated that more than 70% of such adolescents who were infected with HIV perinatally were retained in care 1–2 years post-Health Care Transition.…”
Section: Discussionmentioning
confidence: 99%
“…Youth who perinatally acquired HIV are likely to be retained in HIV care. In a study in United Kingdom, among young adults with perinatally acquired HIV infection that assessed the clinical outcomes post transition to adult services, 86% of these youths were retained in HIV care [ 27 ]. In a systematic review by Ritchwood et al [ 28 ] to examine retention in HIV care, it indicated that more than 70% of such adolescents who were infected with HIV perinatally were retained in care 1–2 years post-Health Care Transition.…”
Section: Discussionmentioning
confidence: 99%
“…APH experience specific challenges due to their life‐long infection and long‐term follow‐up in HIV care [2–6]. They are at risk of inadequate adherence to antiretroviral therapy (ART) [7,8] and poor retention in care during adolescence [9,10]. APH may in turn experience poor health outcomes [11], with a high mortality rate [12,13], virologic failure [14,15] and HIV drug resistance [16], poor growth [17] and immune status [18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, mortality associated with HIV was the eighth leading cause of adolescent deaths globally [ 7 ], but in many settings, following children as they move through paediatric care and transition to adult care is challenging for several reasons, including disjointed health systems and lack of capacity to conduct longitudinal research. Of the studies that have measured mortality in adult care [ 8 , 9 , 10 , 11 , 12 ], some are smaller cohorts that may not be representative of the wider population of young people living with PHIV in their respective setting. The UK benefits from a national paediatric cohort, which includes all children diagnosed with HIV and in paediatric care, embedded within the National Health Service, and an ongoing large observational cohort of adults receiving care for HIV [ 13 , 14 ], We conducted data linkage of these two cohorts, which enabled us to assess the incidence of AIDS events and mortality, as well as identify any risk factors, among young people with HIV who transitioned from paediatric to adult care across clinical settings in the UK.…”
Section: Introductionmentioning
confidence: 99%